UME KBUBU SEBAGAI WUJUD KEARIFAN LOKAL MASYARAKAT BOTI DALAM MENJAGA KETAHANAN PANGAN DAN BENCANA - Iswanto Iswanto (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2021)
Local wisdom defined as the ability of a community to adapt to, organize, and manage the environment and culture that affects their lives. The research conducted in the Boti community of East Nusa Tenggara Province aims to describe and understand ume kbubu as a form of local wisdom of the Boti community in maintaining food security and protecting them from disasters. The method used in this study was a qualitative method with a phenomenological approach. The characteristics of this research data are classified as sensitive research data; therefore, it takes a long time to obtain. Observation and interviews were data collection techniques used in this research. The result indicated that the structure of ume kbubu shows the local wisdom of the Boti community in adapting to the environment and influencing the scattered settlement structures. In addition, the function and symbolization of ume kbubu are closely related to the local wisdom of the community in storing and managing staple food (corn), which is the strength of the Boti community in facing the food crisis. The settlement structure of the Boti community, supported by strict customary rules, becomes a barrier in social interaction that can protect the community from disasters, such as infectious diseases. The local wisdom of the Boti community is likely to be an input for the government to study various cultural aspects to deal with disasters.